The Milk Al-Yamin Concept as a Validity of Sexual Relationship in a Modern Context: an Analysis of Muhammad Syahrur's Thoughts - Hasballah, Khairuddin (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2020)
In the understanding of fiqh turats, the concept of milk al-yamin is affecting the legal protection for oppressed slaves during the Jahiliyah period. According to Syahrur, the concept of milk al-yamin had similarities and differences with the marriage contract. The similarity lies in the ability to have sexual relations, while the difference is that a marriage contract is not merely a sexual relationship, but it has a legal effect on the production of the rights and obligations of a husband and wife to build a family, and other social activities related to mushaharah. Milk al-yamin does not arrive at the emergence of rights and obligations as husband and wife as a result of a marriage contract. The concept of milk al-yamin that Syahrur understands for the present context is how the legal proposition (the Quran) remains suitable with the current era, not to be eradicated historically because it is no longer relevant. He built a new logic for the concept of milk al-yamin in the present context, which is called ‘aqd ihsan. The concept of milk al-yamin understood by Syahrur enables the authorization of contractual marriages or mut'ah which were abolished according to the Sunni school of fiqh. The concept of contract marriage or mut'ah does not have general marriage conditions, because the purpose is not to build a family, but purely sexual relations, and does not belong to the category of formal marriage, although at the same time it is not haram. In consequence, the concept of milk al-yamin is not becoming a basis for legitimizing nonmarital sexual relations.